Description of Patient Satisfaction with the Performance of Health Workers at the Puskesmas Pancur Batu Sub-District - Nuraisyah Wulandari Panjaitan; Indah Doanita Hasibuan; Anita Zahra Putri Purba; Annisa Rizki Ramadani Siregar; Fidella Naily Ulya Hasibuan (PROMOTOR, 2024)
Patient satisfaction is one of the things that must be considered in health services and is an important index or parameter. Patient satisfaction is the result of assessment and consideration of health services in terms of facilities, staff performance, and other aspects provided by patients by comparing expectations with the reality of health services received in a service system. This research aims to determine the description of patient satisfaction with the performance of health workers at the Pancur Batu District Health Center. This research uses a quantitative approach with descriptive methods which aims to express patient satisfaction with the performance of health workers at the District Health Center. Pancur Batu. Based on the research results, a picture of patient satisfaction with the performance of health workers was obtained from several assessments, namely Emphaty, with 30 respondents (100%) feeling satisfied. Furthermore, regarding Assurance, 29 respondents (97%) were satisfied. Furthermore, Tangibles (direct evidence) as many as 28 respondents (93%) were satisfied. Responsiveness with 27 respondents (90%) and Responsiveness with 26 respondents (87%) were satisfied. This research concludes that the majority of patients at the Pancur Batu District Health Center are very satisfied with the performance of the health service employees.